2013
DOI: 10.1016/j.flowmeasinst.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Large probe arrays for measuring mean and time dependent local oil volume fraction and local oil velocity component distributions in inclined oil-in-water flows

Abstract: Arrays of dual-sensor and four-sensor needle conductance probes have been used to measure the mean and time dependent local properties of upward inclined, bubbly oil-in-water flows (also known as dispersed oil-in-water flows) in a 153mm diameter pipe. The flow properties that were measured were (i) the local in-situ oil volume fraction α ; (ii) the local oil velocity o u in the axial direction of the pipe (the Z direction); and (iii) the local oil velocity Y u in the direction from the lower side of the inclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Compared to the literature on air bubble sizing and velocity determination using conductivity or optical-fiber probes, the number of studies on oil droplet sizing and velocity determination in oil-water mixture flows is relatively limited. Among some valuable works [30][31][32][33] employed dual conductivity probes to measure the velocity, volumetric fraction, and size distribution of oil droplets. Using a single cleaved optical-fiber probe [34], first demonstrated the possibility of measuring oil-phase residence time in a vertical kerosene-water mixture flow.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the literature on air bubble sizing and velocity determination using conductivity or optical-fiber probes, the number of studies on oil droplet sizing and velocity determination in oil-water mixture flows is relatively limited. Among some valuable works [30][31][32][33] employed dual conductivity probes to measure the velocity, volumetric fraction, and size distribution of oil droplets. Using a single cleaved optical-fiber probe [34], first demonstrated the possibility of measuring oil-phase residence time in a vertical kerosene-water mixture flow.…”
Section: Introductionmentioning
confidence: 99%
“…For RT#2, however, which assumes that the zero'th order velocity component can be replaced by an axisymmetric distribution of the form given in equation ( 9), the maximum water velocity occurs at some distance below the upper side of the inclined pipe, but above the mid-point of the flow cross section (figures 11(b)-14(b)). One of the authors of the current paper has made a number of exper imental studies of the velocity distributions of the dispersed phases (oil & gas) in upward inclined, water continuous multiphase flows [18][19][20] and has shown that the axial velocity of the dispersed phase is always a maximum at the uppermost side of the inclined pipe. It seems unlikely that this form of velocity distribution should not also apply to the continuous water phase-and hence, for inclined multiphase flows, the water velocity profiles reconstructed using RT#1 are perhaps more representative of the true water velocity profiles than those reconstructed using RT#2.…”
Section: Velocity and Volume Fraction Profiles In Upward Inclined Flowsmentioning
confidence: 97%
“…In addition, more advanced experimental methods are adopted to explore the oil bubble characteristics. The methods such as miniprobe detection [8], high speed photography [9], microwave measurement [10], process tomography [11], and PIV technology [12] have been applied to study the characteristics of oil-in-water two-phase flow.…”
Section: Introductionmentioning
confidence: 99%